Wet-Chemical Noncovalent Functionalization of CVD Graphene: Molecular Doping and Its Effect on Electrolyte-Gated Graphene Field-Effect Transistor Characteristics - Dieng, Mbaye (2022)
raphene sheets (mono- and multilayers) were synthesized by chemical vapor deposition and functionalized with various aromatic molecules such as Fe-/Co-porphyrin and Fe-phthalocyanine through π–π interactions. The resulting nanohybrid materials were characterized by Raman spectroscopy (RS), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), scanning electron microscopy (SEM), and scanning transmission electron microscopy (STEM) techniques. The presence of physi-adsorbed molecules (Fe-/Co-porphyrin and Fe-phthalocyanine) on the graphene sheet surface is evidenced by spectroscopic and microscopic analyses, which confirm that these molecules are immobilized through electrostatic and π–π interactions. RS confirmed the n- or p-type doping of graphene, according to the chemical nature of those physi-adsorbed molecules. The electrical characteristics of electrolyte-gated graphene field-effect transistors (GFETs) based on nanohybrid materials were subsequently evaluated and demonstrated a charge transfer between the physi-adsorbed molecules and the graphene. All of these results suggest that the electronic structure of graphene can be tailored by doping with aromatic molecules. Density functional theory (DFT) calculations were performed to confirm these observations